Apparatus for connection to private circuits run by certain public telecommunication operators. Specification for apparatus for connection to digital circuits with interfaces according to CCITT G-series Recommendations. Section 8.1: G.703 services at 2 048 kbits/s and 8 448 kbits/s Part 8.1, (15th August 2000) - British Standards Institution,
No abstract available